Fly pollination drives convergence of flower coloration. Issue 1 (6th October 2021) - Garcia, Jair E.; Hannah, Lea; Shrestha, Mani; Burd, Martin; Dyer, Adrian G.
Summary: Plant–pollinator interactions provide a natural experiment in signal evolution. Flowers are known to have evolved colour signals that maximise their ease of detection by the visual systems of important pollinators such as bees. Whilst most angiosperms are bee pollinated, our understanding on how the second largest group of pollinating insects, flies, may influence flower colour evolution is limited to the use of categorical models of colour discrimination that do not reflect the small colour differences commonly observed between and within flower species. Here we show by comparing flower signals that occur in different environments including total absence of bees, a mixture of bee and fly pollination within one plant family (Orchidaceae) from a single community, and typical flowers from a broad taxonomic sampling of the same geographic region, that perceptually different colours, empirically measured, do evolve in response to different types of insect pollinators. We show evidence of both convergence among fly‐pollinated floral colours but also of divergence and displacement of colour signals in the absence of bee pollinators. Our findings give an insight into how both ecological and agricultural systems may be affected by changes in pollinator distributions around the world.